The threat of myrtle rust to Maori taonga plant species in New Zealand - Teulon, D.A.J.; Alipia, T.T.; Ropata, H.T.; Green, J.M.; Rollinson, S.L.H. Viljanen-; Cromey, M.G.; Arthur, K.; MacDiarmid, R.M.; Waipara, N.W.; Marsh, A.T. (New Zealand Plant Protection, 2015)
Myrtle rust caused by the pathogen Puccinia psidii is a disease of plants in the Myrtaceae that is currently not known to be present in New Zealand. Its origin is Central/ South America but it has steadily spread around the world and is now found in Australia. All New Zealand Myrtaceae species including indigenous species are at risk from myrtle rust infection but the extent of the impact on plant health is not known. While the potential economic and environmental impacts of myrtle rust establishment in New Zealand have been well documented this paper explores potential sociocultural consequences for Maori. All indigenous Myrtaceae species can be considered as taonga (or treasure) by Maori who have and continue to use the properties of some species in many ways (both tangible and intangible). Preparedness and response plans for a myrtle rust incursion in New Zealand should consider the values that Maori derive from these plants.